Preparation and immunogenicity of conjugate based on hydrazine-treated lipopolysaccharide antigen of Vibrio cholerae O139. Issue 11 (2nd November 2014) - Fleischhackerová, Anna; Farkaš, Pavol; Čížová, Alžbeta; Bystrický, Slavomír
Abstract: A glycoconjugate construct was based on attachment of V. cholerae O139 hydrazine-treated lipopolysaccharide (LPS) to carboxylated bovine serum albumin (CBSA) via its amino group. The immunological properties of the glycoconjugate were tested using BALB/c mice, injected subcutaneously without any adjuvant three times at 2 weeks interval. The immunogenicity of the conjugate was estimated by enzyme-linked immunosorbent assay, testing of anti-LPS IgG, IgM, and IgA antibodies. The conjugate elicited a statistically significant increase of LPS-specific IgG levels in mice ( p  < 0.001). The specific anti-LPS IgG and IgA response after the second booster dose was significantly higher compared with reference and unconjugated detoxified LPS response. Antibodies elicited by the dLPS–CBSA conjugate were vibriocidal. Graphical abstract: : We investigated immunomodulatory properties of prepared glycoconjugate containing 2–3 lipopolysaccharide moieties per one molecule of carboxylated bovine serum albumin.